TINJAUAN YURIDIS PERJANJIAN GADAI DENGAN OBYEK KENDARAAN YANG MASIH TERIKAT PERJANJIAN PEMBIAYAAN KONSUMEN - , PULUNGGONO HANDOKO; , Ninik Darmini, S.H, M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research â review juridical agreement pledge with an object vehicles still tied consumer financing agreement â aims to know legality and due to laws can arise from a pledge made with objects vehicles still tied consumer financing agreement.The study is done because of the practice of making pledge over, the agreement so required an understanding for entrepreneurs pledge and private financing company to be more careful in making covenants. This research is juridical normative, research namely research study on legal norms in agreement. Researchers do 2 (two) research, kinds namely research library and research field. Respondents and sources in this research is private entrepreneurs pledge firm financing, lawyers, and debt collector. Accumulated data qualitative analysis methods and delivered by descriptive. The result showed that the agreement pledge made with objects vehicles still tied consumer financing agreement had no legality.The pledge is ineligible causa being permissible.It is made void and pledge agreement the law. Due to the absence of legality be as follows: firstly, creditor accepter pledge lose the right thing retentie on bail. Secondly, creditor accepter pledge switch free of creditor preferent being konkuren creditors.Thirdly, parties in pledge agreement could be based on rule of criminal law or fiduciary security and kuhp.